Idiom Proficiency of Indonesian EFL Learners: A Quantitative Study of English Department Students in Aceh - Muliawati, Ida; Raisabila, Ulfia; Ayouni, Nour; Jamilah, Sitti (UIBU, 2025)
The research is designed to fill a gap by quantitatively measuring the level of English idiom proficiency into Indonesian equivalent. A descriptive quantitative approach was maginified in analyzing the data obtained from 20 native Acehnese English Department students purposively and voluntarily selected. The instrument employed was in form of a multiple-choice of idiom proficiency test and was analyzed statistically. The findings revealed that English Department students had a moderate level of idiom proficiency by 52.14%. The result indicates that significant number of students demonstrates inadequate comprehension, particularly when encountering idioms that are culturally specific or contextually unfamiliar. Despite their academic background in English and having learning experiences through coursework or translation practice which contribute to help them understand the idioms, challenges remain in dealing with complex cultural meanings, suggesting a gap in both cultural exposure and idiomatic knowledge. Therefore, it is suggested for local educators to develop more effective teaching strategies for figurative language, ultimately enhancing the students’ translational and communicative competence.